A Clinical Study of Drug-Induced Sinus Node Dysfunction - Nakamura, Tetsuya (Nihon Rōnen Igakkai zasshi, 1990)
β blockers and Ca antagonists are popular therapeutic agents for hypertension and ischemic heart disease. Although these are reported to induce various bradycardiac arrhythmias, clincal studies remain insufficient. The author performed a clinical study of sinus node dysfunction caused by drugs for heart and circulatory diseases. Seventy-seven of the 1, 734 patients admitted to the CCU of our hospital during the past 11 years, were the subjects of this study. They showed sinus node dysfunction on electrocardiographs (ECG). Forty-two subjects had drug-induced sinus node dysfunction (DISD) and 35 had sick sinus syndrome (SSS). Rubenstein's classification based on 12-lead ECG was used to diagnose DISD and SSS. All patients underwent chest X-ray examination, ECG, echocardiogram and blood chemistry and were divided into DISD and SSS groups. The DISD group was subdivided into an older group (65 years or more), and a younger group. Ten patients in the DISD group were examined electrophysiologically. SSS II and III types appeared in 22 DISD patients (52.3%) and in 31 SSS patients (88.5%). Bradycardia in the DISD group was milder than in the SSS group, because the DISD group had a higher minimum heart-rate and a shorter maximum R-R interval. However, the DISD group showed significantly lower blood pressure and renal function and a higher grade on the New York Heart Association's (NYHA) classification. Echocardiographic findings following recovery were similar in the two groups. Electrophysiological examination revealed abnormal sinus node function in 3 of the 10 DISD patients (30.0%). In the DISD group, 27 were older patients (3.2%). This was significantly more than the 15 who were younger patients (1.6%). The SSS II and III types appeared in 18 older patients (66.6%) and 4 younger patients (26.6%). The two groups showed no difference in the minimum heart-rate or the maximum R-R interval, but the older group were more severely afflicted, judging from the NYHA classification, renal function and cardiothoracic ratio. The causative drugs were β blockers in 26 patients, Ca antagonists in 21, digitalis in 16 and IA antiarrhythmic drugs in 9. Diltiazem especially had been given to about half of the older patients. Whenever older patients are taking these drugs, we should follow their progress carefully.